Genetic etiology and pregnancy outcomes of fetal hyperechoic kidneys: a retrospective analysis - Cai, Meiying; Lin, Na; Xiao, Ziheng; Huang, Hailong; Zheng, Lin; Xu, Liangpu (Frontiers in Pediatrics, 2025)
BackgroundFetal hyperechoic kidney is an important soft marker in prenatal ultrasonography; however, the causes of this phenomenon are unclear. Therefore, we analyzed genetic diagnosis results, assessed pregnancy outcomes, and conducted postnatal follow-up to provide evidence for prenatal eugenics.MethodsWe retrospectively analyzed data from 94 cases with fetal hyperechoic kidneys identified between November 2017 and January 2024. Chromosome karyotyping and chromosomal microarray analysis (CMA) were performed on fetuses displaying this phenotype on prenatal ultrasound. For cases with normal results from karyotyping and CMA, whole-exome sequencing (WES) was applied.ResultsAmong 94 fetuses with hyperechoic kidneys, five were not subject to chromosome karyotyping owing to gestational age constraints, and one sample failed to culture. Of the remaining 88, karyotyping helped detect six cases with abnormal karyotypes. Among 94 fetuses with hyperechoic kidneys, CMA analysis was performed on 90 fetuses, and 17 cases of abnormal copy number variations (CNVs) were detected. Furthermore, among 82 fetuses with normal karyotypes, 10 additional abnormal CNVs were identified. WES, performed on 13 fetuses with normal chromosomal karyotypes and CMA, helped identify three cases of mutations in HNF1B, NPHP3, and KMT2D. Follow-up of 94 fetuses indicated that 16 were lost to follow-up. Of the 78 followed-up, 25 pregnancies were terminated, and one fetus died in utero. Post-birth follow-up of 52 live births revealed an adverse outcome incidence of 3.85% (2/52), consisting of one neonatal death within 24 h and one case of intellectual disability.ConclusionsCMA is recommended when prenatal ultrasound indicates fetal hyperechoic kidneys. For fetuses with normal CNVs and persistent hyperechoic kidneys, WES is advisable to exclude rare monogenic disorders. In cases of hyperechoic kidneys alongside other ultrasound abnormalities, the live birth rate and prognosis tend to be poor; thus, early genetic screening is essential to guide pregnancy management effectively.